Helsen, Gilis and Weston (2006) err in testing the optical error hypothesis - Oudejans, R. R. D.; Bakker, F. C.; Beek, P. J. (Journal of Sports Sciences, 2006)
In this commentary, we react to the recent study by Helsen, Gilis and Weston (2006) on judging offside in football. Helsen et al. claim that their data falsify the optical error hypothesis presented by Oudejans et al. (2000). However, as we will elucidate here, they misinterpret this hypothesis and present a data set that is seriously flawed, and hence not suited to test it. Therefore, their conclusions regarding the optical error hypothesis are in error.